Reliability of oscillometric central blood pressure responses to lower limb resistance exercise. (January 2018) - Fryer, Simon; Stone, Keeron; Dickson, Tabitha; Faulkner, James; Lambrick, Danielle; Corres, Pablo; Jerred, Lauren; Stoner, Lee
Abstract: Background and aims: Although it is well known that resistance training (RT) is beneficial for patients suffering from a variety of cardiovascular diseases, it remains underutilized as a rehabilitation tool as there is no reliable way to monitor the additional stress placed on the central organs. The current study aimed to determine between-day reliability of central haemodynamic indices using oscillometric pulse wave analysis (PWA) during progressive sub-maximal RT. Methods: Nineteen healthy young males were tested on 3 different mornings in a fasted state. Central hemodynamic variables including augmentation index (AIx), AIx normalized to a heart rate of 75 beats per minute (AIx@75), central systolic blood pressure (cSBP), forwards (Pf) and backwards (Pb) wave reflection were determined at rest, as well as during leg extension RT at 10, 15 and 20% of maximal volitional contraction (MVC), and following 1 min and 5 min passive recovery. Results: During RT at 10, 15 and 20% MVC, the intraclass correlation coefficient (ICC) values for AIx@75 (0.76–0.9), cSBP (0.74–0.78), Pf (0.75–0.82) and Pb (0.75–0.83) exceeded the criteria (0.75) for excellent reliability. During the 5 min recovery, the ICC values for AIx@75 (0.87–0.87), cSBP (0.69–0.7), Pf (0.63–0.67) and Pb (0.63–0.66) indicated good to excellent reliability. Conclusions: Clinically meaningful changes in central hemodynamic indices can be obtained during resistance training using oscillometric PWA devices. This technology holds potential for advancing resistance training prescription guidelines for patients with overt cardiovascular diseases. Highlights: Central blood pressures can be reliably determined during resistance training. Central blood pressures can be reliably determined following resistance training. Oscillometric technology may advance resistance training prescription.